1997
DOI: 10.1093/oxfordjournals.aje.a009074
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acids in Serum Cholesteryl Esters as Quantitative Biomarkers of Dietary Intake in Humans

Abstract: The fatty acid composition of serum cholesteryl esters is used as a qualitative biomarker of fatty acid intake, but quantitative data are scarce. Between 1987 and 1992, the authors fed various fatty acids in four controlled trials to 232 healthy Dutch volunteers and measured the proportion of fatty acids in participants' cholesteryl esters. Each 10% of energy fed as linoleic acid (18:2) raised the proportion of linoleic acid in cholesteryl esters by 9.3 g per 100 g of fatty acids (standard deviation (SD) 3.1).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
122
1
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(135 citation statements)
references
References 48 publications
11
122
1
1
Order By: Relevance
“…The one point assessment of HADS-D on its own might not be enough to measure depression in the present study. (4) A previous study reported that serum FAs were reflected by dietary FA intake in the past 3 weeks (Zock et al, 1997). In the present study, the durations of all subjects between the time points of performing the HADS and blood sampling had a mean value of 3.6 days and standardised deviation of 5.0 days, and those of 95% of all subjects were under 15 days.…”
Section: Serum Fatty Acid and Depression In Cancer Patients M Kobayaksupporting
confidence: 48%
See 1 more Smart Citation
“…The one point assessment of HADS-D on its own might not be enough to measure depression in the present study. (4) A previous study reported that serum FAs were reflected by dietary FA intake in the past 3 weeks (Zock et al, 1997). In the present study, the durations of all subjects between the time points of performing the HADS and blood sampling had a mean value of 3.6 days and standardised deviation of 5.0 days, and those of 95% of all subjects were under 15 days.…”
Section: Serum Fatty Acid and Depression In Cancer Patients M Kobayaksupporting
confidence: 48%
“…Serum FAs were reflected by dietary FA intake in the past 3 weeks (Zock et al, 1997). After storing the samples for about 2 h at 41C, serum was separated by centrifugation (1870g, 10 min), and stored at À801C till measurements (4 -5 years).…”
Section: Measurement Of Fa Composition Of Serum Phospholipidsmentioning
confidence: 99%
“…LDL-fatty acid compositions might not closely reflect fatty acid status as plasma or erythrocyte phospholipids did (Dougherty et al, 1987). But serum cholesteryl ester fatty acid composition has also been widely used as a biomarker for fatty acid intake (Zock et al, 1997). The fatty acids in LDL are predominantly esterified to cholesterol and they contribute to the majority of plasma cholesteryl ester fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acids in serum cholesteryl esters are considered to be quantitative biomarkers of long-term dietary intake in humans (Zock et al, 1997). Both a-linolenic acid and linoleic acid increased after the walnut diet, but the extent was greater for a-linolenic acid (76.3 and 107% for women and men, respectively) than for linoleic acid (7.4 and 9.4% for women and men, respectively).…”
Section: Discussionmentioning
confidence: 99%